2009
DOI: 10.1111/j.1469-8137.2009.03039.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and levels of nonhost resistance to nonadapted Blumeria graminis forms in barley

Abstract: Summary The genetic basis of nonhost resistance of barley to nonadapted formae speciales of Blumeria graminis is not known, as there is no barley line that is susceptible to these nonadapted formae speciales, such as the wheat powdery mildew pathogen, Blumeria graminis f.sp. tritici (Bgt). Barley accessions with rudimentary susceptibility to an isolate of the nonadapted Bgt were identified. Those accessions were intercrossed in two cycles and two lines, called SusBgtSC and SusBgtDC, with substantial suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 36 publications
5
38
0
Order By: Relevance
“…For example, hypersensitive response (HR) is a typical resistance phenomenon that is associated with both R-gene and some nonhost resistance. Similar global gene expression profiles (Tao et al, 2003) and other induced responses (Zimmerli et al, 2004;Aghnoum and Niks, 2010;Zellerhoff et al, 2010;Hiruma et al, 2011) have been observed during nonhost resistance against fungal and bacterial pathogens.…”
mentioning
confidence: 50%
“…For example, hypersensitive response (HR) is a typical resistance phenomenon that is associated with both R-gene and some nonhost resistance. Similar global gene expression profiles (Tao et al, 2003) and other induced responses (Zimmerli et al, 2004;Aghnoum and Niks, 2010;Zellerhoff et al, 2010;Hiruma et al, 2011) have been observed during nonhost resistance against fungal and bacterial pathogens.…”
mentioning
confidence: 50%
“…In the absence of the HR, resistance is achieved by reducing the development of fungal biomass, which may occur by reducing infection rates. Such partial, or ‘horizontal’, resistance has been observed in some cereal rust interactions (Aghnoum and Niks 2010; Marcel et al 2008). One of the best-known ‘slow rusting’ loci is the Lr34/Yr18/Pm38 complex (Singh et al 2007), which confers partial resistance to stripe rust, leaf rust and powdery mildew.…”
Section: Discussionmentioning
confidence: 86%
“…The histological observations showed a general decline in the frequency of pathogen attacks stopped by papilla formation in the epidermal cells of the GPHb1 plants. The reduction was most significant for the interaction with the wheat‐adapted H8 isolate, probably because papilla formation is the main response in barley against nonadapted genotypes (Aghnoum & Niks, ). The reduction in papilla formation did not lead to more established infection sites, but instead to an increase in the percentage of penetrated host cells showing HR as a second line of defence.…”
Section: Discussionmentioning
confidence: 99%